One or two cyclicity inductions on TAI pregnancy rate and pregnancy loss in precocious Nellore heifers - Amanda Alves Rosa Taveira; Lucas Gomes da Silva; Luana Gomes da Silva; Julia Mascharello; Luiz Carlos Lousada Ferreira; Ériklis Nogueira (Ciência Rural)
ABSTRACT: The objective was to evaluate the pregnancy rate and pregnancy loss of precocious Nellore heifers submitted to one or two previous cyclicity inductions to TAI (timed artificial insemination). A total of 572 Nellore nulliparous aged 12 to 14 months-old were used, divided into two treatments: on D-50, T1- one cyclicity induction (n = 313): 1 ml of 0.9% NaCl and T2- two cyclicity induction (n = 259): 1 ml of injectable progesterone. From that date, the two groups received the same management as follows: On D-26, oral supply of 2.28 g/head/day (MGA® PREMIX) for twelve days and on D-12, IM application 0.6 mg of estradiol cypionate (E.C.P.®) in all. Subsequently carried out the TAI protocol and pregnancy diagnosis was performed on D41 and pregnancy confirmed on D101. The uterus and ovary were evaluated in D-50, D-26, and D0. There was no difference in pregnancy rate and pregnancy loss (P > 0.05), besides in T2, better grades of uterine and ovarian scores were observed between the beginning of cyclicity induction and D0 (P < 0.05). The two-induction group had better uterus and ovary scores, which did not interfere with pregnancy and pregnancy loss rates.